EFEKTIVITAS PUSAT PEMBELAJARAN KELUARGA (PUSPAGA) DALAM PENCEGAHAN KASUS KEKERASAN PADA ANAK DI TANGERANG SELATAN - Taufiq Ramadhan; Naziah Diniyah (Universitas Darunnajah Jakarta, Indonesia, 2022)
Children play a vital role as future generations to come. Parents lovingly instill in their children the virtues of kindness. Good parenting can affect a child's moral development as an adult. Violence against the child is behavior that can harm the child either physically or mentally. The prevalence of violence against this child is largely a factor in the family. Furthermore, there is a shortage of knowledge regarding child upbringing. In Indonesia there are various institutions where counseling or institution may be a means of consulting on family issues in order to prevent a particularly violent case of children. It is the center for family learning (puspaga), which is under the protection of Child And Family Protection Women's Empowerment Service (DP3AKB). The research approach USES qualitative analysis descriptive methods, is supported by primary and secondary data-collection techniques, then observation, interview and document studies, and then testing the validity of the data using field observation and documents to make it more credible. Studies have shown that PUSPAGA'S implementation of programs in the prevention of violent cases of children works well, since the implementation of programs is consistent with both ends and objectives. Moreover, in the process of counseling services through a process of analysis which should not be arbitrarily addressing a problem. As for the constraints that come with the lack of manpower in institutions and time. But from these porgrames and services at the center for the prevention of child violence are effective, because the action programs are consistent and have the clarity of purpose they want to achieve, and have the appropriate analysis and formulation of policies in dealing with client problems.